(untitled) (EAAE Annual Conference Proceedings, 2023)
Transformations of public spaces are an integral part of city life. These processes although addressing site specific problems are universal for the urban centres across European countries struggling with desurbanisation, social exclusion, massive tourism, climate change and pollution.